PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KOMPLEKSITAS PEMERINTAH DAERAH DAN TINDAK LANJUT REKOMENDASI HASIL PEMERIKSAAN BPK TERHADAP TEMUAN KELEMAHAN PENGENDALIAN INTERN PEMERINTAH DAERAH (Studi Empiris Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah) - Fatin Riski Amalia; Agus Purwanto (Diponegoro Journal of Accounting, 2023)
This study aims to examine and obtain empirical evidence on the effect of the use of information technology, the complexity of the local government and the follow-up recommendations of audit results of the BPK on the findings of weaknesses in the internal control of district or city local governments in Central Java.The data population uses the district or city government in Central Java Province. The sample selection method using the purposive sampling method obtained as many as 117 samples with data sources from LHP on LKPD for data on findings of internal control weaknesses, the number of SKPD obtained from LHP on LKPD, SPBE values for data from KemenPAN-RB, e-government values from Diskominfo and TLRHP from BPK RI TLRHP report. Hypothesis testing was carried out using multiple linear regression analysis.The results obtained in this study indicate that the use of information technology and follow-up on the recommendations of audit results affect on the findings of weaknesses in the internal control of district or city local governments in Central Java Province. Meanwhile, the complexity of the local government does not influence the findings of weaknesses in the internal control of district or city local governments in Central Java Province.